Elevated high-mobility group B1 levels in active adult-onset Still's disease associated with systemic score and skin rash. Issue 8 (August 2016) - Jung, Ju-Yang; Suh, Chang-Hee; Sohn, Seonghyang; Nam, Jin-Young; Kim, Hyoun-Ah
Abstract High-mobility group box-1 (HMGB1) is a nuclear protein, and such prototypical damage-associated molecular patterns mediate the immune response in the noninfectious inflammatory response. Adult-onset Still's disease (AOSD) is a systemic inflammatory disorder involved in the dysregulation of innate immunity. We investigated the serum HMGB1 level in patients with AOSD and evaluated its clinical significance. Blood samples were collected from 40 patients with active AOSD and 40 healthy controls (HC). Of the patients with AOSD, follow-up samples were collected from 16 patients after a resolution of AOSD disease activity. Serum HMGB1 levels in patients with AOSD were higher than those of the HC (10.0 ± 5.85 vs. 5.15 ± 1.79 ng/mL, p < 0.001). Serum HMGB1 levels were found to be correlated with C-reactive protein (CRP) and the systemic score. The AOSD patient who had a sore throat showed a higher serum HMGB1 level than those patients who did not, and the patient with a skin rash had higher levels than the patients without. In addition, the serum HMGB1 levels were decreased after the resolution of disease activity in the AOSD patients who were followed up. The serum HMGB1 levels were elevated in AOSD patients compared to the HC and were correlated with both CRP and the systemic score. The HMGB1 levels were associated with skin rash and a sore throat in AOSD patients. After the resolution of disease activity, serum HMGB1 levels were found to have decreased.